Teaching and learning engineering software - Er, Chao Xing (2011)
This report documents the process in developing the teaching tool for Mechanics of Engineering Materials. Through a careful study of the different developmental costs of an effective learning module, this project’s development is justified by a cost comparison of the traditional instructor-led training with the proposed e-learning model.